Analisa Situasi Kesakitan Demam Berdarah Dengue Kabupaten Cirebon PeriodeTahun 2006-2008 - Lukman Hakim; Herra Superiyatna (ASPIRATOR - Journal of Vector-borne Disease Studies, 2009)
Abstracts. Cirebon regency is one of highest endemic area of dengue hemorrhagic fever(DHF) at West Java. during three the last year, there are 4.199 cases, that is 1.535 cases inyear 2006 (incidence rate/IR = 0,732‰), 1.523 cases in year 2007 (IR = 0,712‰) and 1.141cases in year 2008 (IR = 0,523‰).To get DHF epidemiology information at Cirebon regency had been done a data analysisthat aimed to know epidemiology description and risk factor identification related to casedistribution (person, time and place variables).Data analysis was resulted that there are depreciation of DHF case in year 2007 when comparedwith year 2006 and also case in the year 2008 compared with year 2007, but as awhole DF cases at Cirebon regency still high.Proportion of DHF cases in male is not differing compared female. It based on age group,highest cases is 15 - 45 year group that be a voluminous age group with high mobility.Thereby, DHF transmission is guessed happened in outside of residence areas may be atschool or at work areas.Data analysis also founding there are associate between rain falls with DHF case incident,although that is a weak association. The peak of incident cases is happened in January(transmission peak in December.